Characterizing the Macrocyclization Activity of Fungal Polyketide Synthase Thioesterases - Wirz, Monica Hélène (Université d'Ottawa / University of Ottawa, 2012)
Fungal polyketides are a diverse class of natural products that possess many pharmacological properties, including anticancer properties. These properties are evident in the resorcylic acid lactones, a family of polyketides, including zearalenone and radicicol, which shows potent inhibition of tumour cell growth. The key step in the biosynthesis of these lactones is macrocyclization of a linear carboxylic acid into the macrolactone. This reaction is catalyzed by a polyketide synthase (PKS) thioesterase enzyme. Bacterial PKS thioesterases (TEs) have been extensively studied and their substrate specificity has been characterized in vitro. They are highly substrate selective for the macrocyclization reaction. Since Fungal PKS TEs show little sequence homology to bacterial TEs, we have begun investigating their substrate specificity. In particular we are examining the ability of fungal TEs to macrocyclize compounds with varying ring sizes, stereogenic configuration, and nucleophiles. Herein we present the synthesis of a number of diverse TE substrates and the in vitro macrocyclization results for the TEs from zearalenone and radicicol biosynthetic pathway with these substrates.
Keywords: macrocyclization; polyketide; thioesterase; biosynthesis; chemoenzymatic; Natural product chemistry